Effect of phenolic resin content in waste foundry sand on mechanical properties of cement mortars and leaching of phenols behaviour - de Paiva, Fábio Friol Guedes; dos Santos, Luis Fernando [UNESP]; Tamashiro, Jacqueline Roberta; Pereira Silva, Lucas Henrique; Teixeira, Silvio Rainho [UNESP]; Galvín, Adela P.; López-Uceda, Antonio; Kinoshita, Angela (Elsevier, 2023)
Waste foundry sand (WFS) is usually a sand substitute in cementitious materials. However, some of them are contaminated with phenolic resin (WFPS) and there are few papers about it, due to difficulties to reuse. This work focuses on mortar with WFPS as a candidate to immobilize phenolic resin and their environmental safety, since phenols are hazardous materials. Two different WFPS, with low and high resin contents, and a third, with alkaline treatment, were studied. Mortar with WFPS with low resin content reached satisfactory mechanical strength while with the high resin content presented a reduction of up to 50%. The leaching of phenols by WFPS with high resin contents reached up to 20 times the normative limit. However, the leaching of phenols of mortar, in the monolithic state, in long-term is within the limits, demonstrating the possibility of recycling this waste produced in large quantities worldwide by foundry industries.
Keywords: Cementitious composites; Environmental assessment; Phenolic resin; Sand replacement; WFS